1
$\begingroup$

I've been having a hard time to applicate Girsanov theorem with Radon-Nikodym derivative in the demonstration of German-El Karoui-Rochet formule.

I know that $\Pi_0:=S_0\mathbb{Q}^S(S_T\geq K)-K\mathbb{Q}^T(S_T\geq K)P(0,T)$. I have to calculate these two probabilities. I start from the second assuming that the procedure is the same for the first.

Let $Z_t:=\frac{S_t}{P(t,T)}$ a process under physical measure $\mathbb{P}$ and dynamics $dZ_t:=Z_t[u_t^zdt+\sigma_t^zdW_t]$. Since the process is $(\Omega,F,\mathbb{P})$-definited while the probability to calculate is $\mathbb{Q}^T$-definited, i have to apply a change of measure with Girsanov theorem. I know that Girsanov allows me to construct (through Radon-Nikodym derivative expressed in terms of exponential martingale: $L(\omega):=\frac{d\mathbb{Q}^T}{d\mathbb{P}}:=M_t\Rightarrow E^{\mathbb{Q}^T}[X]=E^{\mathbb{P}}[M_tX]$) a martingale measure $\mathbb{Q}^T$ equivalent to the physical measure in such a way that the process $\tilde{W_t}$ under the new measure is a Brownian Motion standard. Let $P(T,T):=1$, i start saying that:

$\mathbb{Q}^T(S_T\geq K)=\mathbb{Q}^T(\frac{S_T}{1}\geq K)=\mathbb{Q}^T(\frac{S_T}{P(T,T)}\geq K)=\mathbb{Q}^T(Z_T\geq K)$

Now the problems.

Given that to do the change of measure it's true that $E^{\mathbb{Q}^T}[Z_T]=E^{\mathbb{P}}[M_tZ_T]$, i thought that the $\mathbb{Q}^T$-martingale resulting should have, for definition, a dynamics contains only diffusive part. Formerly: $d\mathbb{Z}_t^{\mathbb{Q}^T}=\sigma_t^zd\tilde{W}_t$ . However the text (very incomplete, actually) says the dynamics of $Z_t$ under $\mathbb{Q}^T$ measure is $d\mathbb{Z}_t^{\mathbb{Q}^T}=Z_t\sigma_t^zd\tilde{W}_t$.

I thought to applicate the Fundamental Theorem of change of numeraire saying that, since $P(t,T)$ fulfils the conditions of theorem (always assumes values strictly positive and is a $\mathbb{Q}$-martingale for the First Fundamental Theorem of APT), for the change of numeraire $Z_t:=\frac{S_t}{P(t,T)}$ is a $\mathbb{Q}^T$-martingale. But this would contradict the hypothesis in which the process is $\mathbb{P}$-definited.

I tried to apply the Ito's formule to $Z_T^{\mathbb{Q}^T}=\left ( Z_Te^{\int_{0}^{T}\sigma_s^zdW_s-\frac{1}{2}\int_{0}^{T}(\sigma_s^z)^2ds} \right )^{\mathbb{P}}$ (in according to the change of measure) but i dont'understand why the text fixed the stochastic integral $dW_s$ under $\mathbb{Q}^T$: this contradict not only the change of measure with Radon-Nikodym measure but the definition of exponential martingale, that is a process $\mathbb{P}$-definited.

Anyway, I can't derive the result that is $\mathbb{Q}^T(S_T\geq K)=\mathbb{Q}^T(-\tilde{Y}\leq \frac{ln(\frac{S_0}{KP(0,T)})-\frac{1}{2}\sum ^2}{\sqrt{\sum ^2}})$, where:

  1. $\sum ^2=\int_{0}^{T}(\sigma_s^z)^2ds$;
  2. $\tilde{Y}$ is the standardization of $Y:=e^{\int_{0}^{T}\sigma_s^zdW_s-\frac{1}{2}\int_{0}^{T}(\sigma_s^z)^2ds}$ (with $dW_s$ under $\mathbb{Q}^T$).

Any help would be really welcome. Thanks!

$\endgroup$
1
$\begingroup$

The definition of $Z$ tell us that the process $\lbrace{Z_t\rbrace}_{t\geq0}$ is a martingale under the $T-$forward measure $\mathbb{Q}^T$. Given the dynamic of $Z$, we can find out the Radon-Nikodym derivative. \begin{align*} dZ_t &= Z_t\left(u_t^zdt + \sigma_t^zdW_t \right) \\ &= Z_t\sigma_t^z\left(dW_t + \frac{u_t^z}{\sigma_t^z}dt \right) \\ &= Z_t\sigma_t^zd\bar{W}_t \quad \quad (1) \end{align*} where $\bar{W}$ is a $\mathbb{Q}^T$ Brownian motion. Therefore, we can construct the R-N measure which is \begin{equation*} M_t = \exp\left(-\frac12\int_0^t \left(\frac{u_s^z}{\sigma_s^z}\right)^2ds - \int_0^t \frac{u_s^z}{\sigma_s^z}dW_s\right) \end{equation*} Now we have all the ingredients to compute $\mathbb{Q}^T(S_T \geq K)$. \begin{align*} \mathbb{Q}^T(S_T \geq K) &= \mathbb{Q}^T(Z_T \geq K) \\ &=\mathbb{Q}^T\left(Z_0\exp\left(-\frac12\int_0^T(\sigma_s^z)^2ds + \int_0^T \sigma_s^zdW_s\right) \geq K\right)\\ &=\mathbb{Q}^T\left(\int_0^T \sigma_s^zd\bar{W}_s \geq \log\left(\frac{K}{Z_0}\right) + \frac12\Sigma^2\right) \\ &=\mathbb{Q}^T\left(\tilde{Y} \geq \frac{\log\left(\frac{K}{Z_0}\right) + \frac12\Sigma^2}{\Sigma}\right) \\ &=\mathbb{Q}^T\left(-\tilde{Y} \leq \frac{\log\left(\frac{S_0}{KP(0,T)}\right) - \frac12\Sigma^2}{\Sigma}\right) \end{align*} The fourth equality follows from the fact that $\lbrace{\int_0^t \sigma_s^zd\bar{W}_s\rbrace}_{t\geq0}$ is a Wiener process under the measure $\mathbb{Q}^T$. Hence, it follows a gaussian distribution with mean $0$ and variance $\Sigma$.

Some observations on your post :

  1. $Z$ is a lognormal process under $\mathbb{P}$ as well as under $\mathbb{Q}^T$. Hence, one cannot have $dZ_t = \sigma_t^zd\bar{W}_t$ (which is btw a normal process). That being said, you are right that under $\mathbb{Q}^T$ the process $Z$ is a real martingale and should only have the diffusive part (no finite variation process) and it is case in (1).
  2. Often a numeraire, say $Y$, is chosen for a given process, say $X$, such that $X$ becomes a martingale under a new measure called the martingale measure associated to the numeraire $Y$. As noted, $Y$ has to fulfill some conditions to be a numeraire.
$\endgroup$
  • $\begingroup$ @ Sesame: Thanks so much for your answer. I take this opportunity to clearing another aspect. If passing from $\mathbb{P}$ to $\mathbb{Q}$ means applying $\frac{d\mathbb{Q}}{d\mathbb{P}}=M_t=e^{\int_{0}^{t}z_sdW_s^{\mathbb{Q}}-\frac{1}{2}\int_{0}^{t}z_s^2ds}$ with $W_t^{\mathbb{Q}}=W_t-\int_{0}^{t}z_sds$, is correct saying that for passing from $\mathbb{Q}$ to $\mathbb{P}$ means applying $\frac{d\mathbb{P}}{d\mathbb{Q}}=M_T^{-1}=e^{-\int_{0}^{t}z_sdW_s^{\mathbb{P}}+\frac{1}{2}\int_{0}^{t}z_s^2ds}$ with $W_t^{\mathbb{Q}}=W_t+\int_{0}^{t}z_sds$? I get confused with the signs. $\endgroup$ – Marco Pittella Apr 26 at 14:09
  • 1
    $\begingroup$ If $\mathbb{P} \sim \mathbb{Q}$, then there exists a strictly positive process $(\mathbb{P}, F)$-martingale $M_t$ for $t \leq T$ such that $\frac{d\mathbb{Q}}{d\mathbb{P}} = M_t$. Plus, $M_0 = 1$ and $E_{ \mathbb{P}}[M_t] = 1, \forall t \leq T$. Thus, we need to have $E_{\mathbb{P}}[\frac{d\mathbb{Q}}{d\mathbb{P}}]=1$ or $E_{\mathbb{Q}}[\frac{d\mathbb{P}}{d\mathbb{Q}}]=1$. In your case, we don't have this unless we express the Brownians in the right measure. Informally, if $d\mathbb{Q} = M_td\mathbb{P}$ then we use $W_t^{{P}}$ and if $d\mathbb{P} = M_t^{-1}d\mathbb{Q}$ then we use $W_t^{{Q}}$ $\endgroup$ – Sesame Apr 26 at 14:49
  • $\begingroup$ For precision, we have 1.$\frac{d\mathbb{Q}}{d\mathbb{P}} = M_t = e^{- \frac12\int_0^tz_s^2ds +\int_0^tz_sdW_s^{\mathbb{P}}}$ 2. $\frac{d\mathbb{P}}{d\mathbb{Q}} = M_t^{-1} = e^{- \frac12\int_0^tz_s^2ds -\int_0^tz_sdW_s^{\mathbb{Q}}}$ $\endgroup$ – Sesame Apr 26 at 14:57
  • $\begingroup$ @ Sesame: I don't understand two things: 1) If $dW_t^{\mathbb{Q}^T}=dW_t+\frac{\mu_t^z}{\sigma_t^z}dt\Rightarrow W_t^{\mathbb{Q}^T}=W_t+\int_{0}^{t}\frac{\mu_s^z}{\sigma_s^z}ds$, so $\frac{d\mathbb{P}}{d\mathbb{Q}^T}=e^{-\int_{0}^{t}z_sdW_s^{\mathbb{Q}}-\frac{1}{2}\int_{0}^{t}z_s^2ds}=e^{-\int_{0}^{t}\frac{\mu_s^z}{\sigma_s^z}(dW_s+\frac{\mu_s^z}{\sigma_s^z}ds)-\frac{1}{2}\int_{0}^{t}(\frac{\mu_s^z}{\sigma_s^z})^2ds}=e^{-\int_{0}^{t}\frac{\mu_s^z}{\sigma_s^z}dW_t-\frac{3}{2}\int_{0}^{t}(\frac{\mu_s^z}{\sigma_s^z})^2ds}$. Where I wrong? 2) What happened to $\mu_s^z$ in the numerator? $\endgroup$ – Marco Pittella Apr 26 at 18:27
  • $\begingroup$ 1. This is correct. But I don't see why you need to express the BM in the measure $\mathbb{P}$. In your precise case, we are only interested in the measure $\mathbb{Q}^T$. Read my previous comment. 2. What do you mean by that ? $\endgroup$ – Sesame Apr 26 at 18:37

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.